Design of a solar water pumping system for efficient irrigation systems for crop production - Ani, Vincent Anayochukwu (Frontiers in Sustainable Food Systems, 2025)
Agriculture is the lifeblood of human civilization, providing sustenance and livelihoods to billions worldwide. Solar power solutions are emerging in agriculture to make the industry more sustainable in the future. In Karshi village, Abuja, Nigeria, a large percentage of the population earns their living from agriculture and many small-scale farmers rely on it for their only source of income. Most farmers in this community practice crop rotation, and a key challenge they face is ensuring energy access for pumping solutions. Therefore, there is a need for a solar-powered water pumping system to be designed for irrigation systems on farms in Karshi-Abuja. The method for this study is research through case studies at different farm sites in the communities of Abuja and surrounding areas; the results indicate that the daily water demand for crop irrigation in Karshi was 10,000 litres per day for a field size of one hectare. A pump is required to supply water from a well to an elevated water storage tank. A pump that could supply a flow rate of 2.4 m3/hour at a Total Dynamic Head (TDH) of 14.2 meters was chosen. Upon analyzing the pump curves, it was observed that the pump motor needs approximately 258 W of power to reach the desired performance. After reviewing various solar panel options on the market, a solar panel with the appropriate configuration (peak power of 110 W, operating voltage of 18.8 V, and operating current of 5.9 A) was chosen. An array of three 110-watt solar panels wired in parallel was used to produce a current of 17.7 A with a total output power of 330 W, which should suffice to power the pump.